THE PLACE AND CHARACTERISTICS OF RELIGIOUS DISCOURSE IN THE SYSTEM OF COMMUNICATION FORMS (Universal International Scientific Journal, 2026)
This article analyzes the place of religious discourse in the system of communication forms and its specific linguistic and communicative features. The study theoretically sheds light on the essence of religious discourse as a socio-cultural phenomenon, its functions in the communicative process, and its relationship with other types of discourse. It also scientifically analyzes the communicative subjects participating in religious discourse, speech strategies, the genre system, and the main features of religious speech, such as affectivity, sacredness, and institutionality. The results of the study serve to determine the place of religious discourse in the communication process and to shed more light on its linguistic and functional features.
Keywords: : religious discourse, communication, forms of communication, discourse genre, institutional discourse, communicative strategy, religious discourse, linguistic features, socio-cultural factors